2014
DOI: 10.1002/hbm.22518
|View full text |Cite
|
Sign up to set email alerts
|

Movement‐related neuromagnetic fields in preschool age children

Abstract: We examined sensorimotor brain activity associated with voluntary movements in preschool children using a customized pediatric magnetoencephalographic system. A videogame-like task was used to generate self-initiated right or left index finger movements in 17 healthy right-handed subjects (8 females, ages 3.2-4.8 years). We successfully identified spatiotemporal patterns of movement-related brain activity in 15/17 children using beamformer source analysis and surrogate MRI spatial normalization. Readiness fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 79 publications
9
60
1
Order By: Relevance
“…In a study of 12-to 18-month-old infants, Travis et al ( 2011 ) found evidence of adult-like patterns of left-lateralized frontotemporal activation during lexical-semantic processing, suggesting that this region supports word learning from infancy. Contrary to the adult-like activation patterns observed in relation to language processing among young children, sensory-motor behavior performed during MEG evinces activation patterns which signifi cantly differ from those seen in older children and adults (Cheyne, Jobst, Tesan, Crain, & Johnson, 2014 …”
Section: Content Area 1: the Context Of Therapy Practice In Schoolscontrasting
confidence: 74%
“…In a study of 12-to 18-month-old infants, Travis et al ( 2011 ) found evidence of adult-like patterns of left-lateralized frontotemporal activation during lexical-semantic processing, suggesting that this region supports word learning from infancy. Contrary to the adult-like activation patterns observed in relation to language processing among young children, sensory-motor behavior performed during MEG evinces activation patterns which signifi cantly differ from those seen in older children and adults (Cheyne, Jobst, Tesan, Crain, & Johnson, 2014 …”
Section: Content Area 1: the Context Of Therapy Practice In Schoolscontrasting
confidence: 74%
“…The authors concluded that these findings may indicate that children exhibit decreased motor cortical inhibition relative to adolescents and adults. In addition, Cheyne et al (2014) reported that the transition between immature and adult-like cortical responses associated with motor tasks occurs between 3–5 and 8 years old, as preschool children under 5 years old exhibited significantly different patterns of MRCFs associated with self-initiated index finger movement in comparison to older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The grey matter changes are presumed to be related to the synaptic pruning that is associated with the optimization of the neuronal groups that comprise the sensorimotor cortices. Recent investigations have also shown that children have less prominent changes in the sensorimotor cortical oscillations at the beta frequency (15–30 Hz) during the motor planning period and may recruit compensatory cortical areas when formulating a motor plan (Cheyne, Jobst, Tesan, Crain, & Johnson, 2014; Pangelinan, Kagerer, Momen, Hatfield, & Clark, 2011; Wilson et al, 2010). Further interrogation of the relationship between the cortical dynamics while performing a leg target matching task may provide unique insight on why children tend to take longer to plan, have greater errors and take longer to match a given target.…”
Section: Discussionmentioning
confidence: 99%